ELABORAÇÃO DO OBJETO DE APRENDIZAGEM PARA TRATAMENTO DA INFORMAÇÃO: A MATEMÁTICA NA MODA - Colbek, Rudieri T.; Pereira, Tânia M.; Costa, Juliane S. P.; Prestes, Eduardo; Neumann, Lorilei; Trentin, Rafaela (Salão do Conhecimento, 2013)
Resumo